What Do We Know About Tariff Incidence? - Tokarick, Stephen (IMF Working Papers; Working Paper ;, 2004)
This paper examines the question: Who bears the larger portion of the excess burden of a tariff-the country that imposes it, or a country that it trades with? For a country that can influence its terms of trade, there are two ways of approaching this question. This paper shows that under certain assumptions, the extra burden from a marginal change in the homecountry tariff is shared equally between the home and foreign country at a tariff rate equal to twice the optimal tariff for the home country. Also, the cumulative welfare effect of a tariff in the home country, relative to free trade, turns out to be equalized across countries when the home tariff equals four times its optimal tariff. The paper provides an application of these results and points policymakers to the types of data that are relevant if they want to negotiate over "burden sharing.".